2006
DOI: 10.17221/3658-cjgpb
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal effects on In Vitro morphogenesis in Wheat intervarietal Substitution Lines

Abstract: Common and dwarf bunt (Tilletia caries (DC.) Tul & C. Tul, T. foetida (Wallr.) Liro and T. controversa (Kühn) are potentially important wheat diseases in Romania, especially in organic farming and on small farms, unable in most cases to properly treat the seed. Growing bunt resistant cultivars can be an efficient way to reduce expenses and protect the environment, by reducing use of pesticides. For these reasons, a small breeding program was started in 1972, by crossing the old Turkish wheat PI 178383 (a Bt9 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Most of the utility plant traits are polygenically-controlled quantitative traits. Reports based on the results of many authors indicate that the morphogenetic potential of plant cells and tissues is also a quantitative and, therefore, polygenic trait (Oleszczuk and Zimny 2000;Li et al 2003;Tyankova et al 2006;Dodig et al 2008). The genotype of the primary explant is the most important factor determining the effective regeneration of plants from callus in various monocotyledonous plant species (Mathias 1990;Li et al 2003).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most of the utility plant traits are polygenically-controlled quantitative traits. Reports based on the results of many authors indicate that the morphogenetic potential of plant cells and tissues is also a quantitative and, therefore, polygenic trait (Oleszczuk and Zimny 2000;Li et al 2003;Tyankova et al 2006;Dodig et al 2008). The genotype of the primary explant is the most important factor determining the effective regeneration of plants from callus in various monocotyledonous plant species (Mathias 1990;Li et al 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Bhaskaran and Smith (1990) and Bregitzer and Campbell (2001) found that in vitro cereal morphogenetic abilities are inherited quantitatively. Tyankova et al (2006) and Oleszczuk and Zimny (2000) reported that the morphogenetic potential of plant cells and tissues was a quantitative trait, and thus polygenically determined. Hence, a thorough understanding of its genetic determinants is difficult and requires observation of the phenotypic expression of the trait in numerous populations and to conduct many genetic analyses using special research methods.…”
Section: Introductionmentioning
confidence: 99%
“…Reports based on the results of many authors indicate that the morphogenetic potential of plant cells and tissues is also a quantitative and, therefore, polygenic trait (Dodig, Zorić, Mitić, Nikolić, & Surlan‐Momirović, ; Li et al., ; Oleszczuk & Zimny, ; Tyankova et al., ). The results of the research carried out in this work also confirm the quantitative nature of morphogenetic potential inheritance of Fragaria vesca cultivars analysed in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…Bhaskaran and Smith () and Bregitzer and Campbell () found that in vitro cereal morphogenetic abilities are inherited quantitatively. Oleszczuk and Zimny () and Tyankova, Zagorska, Chardakov, Dryanova, and Dimitrov () also have reported that the morphogenetic potential of plant cells and tissues is quantitative, and thus a polygenically determined trait. Hence, a thorough understanding of its genetic determinants is difficult and requires observation of the phenotypic expression of the trait in numerous populations and conducting many genetic analyses using special research methods.…”
Section: Introductionmentioning
confidence: 99%